2015
DOI: 10.1158/1535-7163.mct-14-0456
|View full text |Cite
|
Sign up to set email alerts
|

Combining Onartuzumab with Erlotinib Inhibits Growth of Non–Small Cell Lung Cancer with Activating EGFR Mutations and HGF Overexpression

Abstract: Erlotinib, a tyrosine kinase inhibitor of the epidermal growth factor receptor (EGFR-TKI), benefits survival of patients with non-small cell lung cancer (NSCLC) who harbor activating EGFR mutations. However, elevated expression of hepatocyte growth factor (HGF), a ligand of the MET receptor tyrosine kinase, causes erlotinib resistance. Because onartuzumab, a monovalent antibody to MET, blocks HGF-induced MET activation, the addition of onartuzumab to erlotinib may improve therapeutic efficacy. We engineered th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…Moreover, the presence of HGF can accelerate NSCLC‐cell resistance to EGFR TKIs by promoting clonal selection of a subpopulation of cells with c‐Met amplification . Preclinical studies in human lung cancer cell lines and lung tumor xenografts in transgenic mice have shown promising results with dual HGF/c‐Met and EGFR inhibition, including additive antitumor activity and restoration of EGFR‐TKI sensitivity . Taken together, these results indicate that combined EGFR and HGF/c‐Met inhibition is a promising strategy to overcome intrinsic and acquired resistance and thereby to improve the outcomes of NSCLC patients.…”
mentioning
confidence: 90%
“…Moreover, the presence of HGF can accelerate NSCLC‐cell resistance to EGFR TKIs by promoting clonal selection of a subpopulation of cells with c‐Met amplification . Preclinical studies in human lung cancer cell lines and lung tumor xenografts in transgenic mice have shown promising results with dual HGF/c‐Met and EGFR inhibition, including additive antitumor activity and restoration of EGFR‐TKI sensitivity . Taken together, these results indicate that combined EGFR and HGF/c‐Met inhibition is a promising strategy to overcome intrinsic and acquired resistance and thereby to improve the outcomes of NSCLC patients.…”
mentioning
confidence: 90%
“…Therefore, the development of a new generation of EGFR-TKI and cMET inhibitors represents a critical strategy for overcoming EGFR-TKI resistance in NSCLC. 11, 12, 13, 14, 15, 16, 17, 18, 19 Unfortunately, EGFR-independent mechanisms of acquired resistance to AZD9291, a third-generation TKI, have already been reported in EGFR-E790M-positive NSCLC patients. 20 …”
mentioning
confidence: 99%
“…The doses of ATL-1 used were based on another study, which showed significant inhibitory effects on tumor growth without noticeable toxicity [38]. In addition, the combination of erlotinib with other agents, showing even greater effects in inhibition of human cancer cells through multiple molecular mechanisms, have also been reported in other studies [54][55][56]. Our findings suggest that ATL-1 might sensitize or enhance the effect of erlotinib in the controlling human lung cancer cell growth or vice versa via targeting the tumor suppressor target genes PDK1 and EZH2 [57], and HOTAIR signaling axis.…”
Section: Discussionmentioning
confidence: 99%